Inclusion of wheel slips in mobile robot modelling to enhance robot simulator performance - Sidek, Shahrul Na'im; Sarkar, Nilanjan (2008)
Improving navigation performance of autonomous wheeled mobile robot (WMR) in a dynamic unstructured environment requires improved maneuverability. In such cases, the dynamics of wheel slip may violate the ideal no-slip kinematic constraints generally used to model nonholonomic WMR. In this paper, a new method is proposed to tackle the modeling inadequacy that arises when slip is neglected by including both longitudinal and lateral slip dynamics into the overall dynamics of the WMR. The new model provides a realistic simulation environment that can be utilized to develop a better model-based controller to improve WMR navigation especially when the WMR is to be driven autonomously at high speed on unstructured environment. We argue that wheel slip is an important factor that can impact WMR navigation performance in such an application.